Puntualizaciones sobre «La transición». Apropósito de un encuentro reciente - Bravo, Gonzalo (Gerión. Revista de Historia Antigua, 1994)
The object of this article is in fact a review of a spanish contribution to the topic on the ways from Antiquity to mediaeval times, in short, on the « transition». Ten studies are here presented, resumed and, if it is necessary, criticized with own references to its pages, where such affirmations are realized. There is also a up-date point of view on the late Antiquity and beyond.